Time Series Analysis Indicators under Directional Changes: The Case of Saudi Stock Market - Aloud, Monira Essa (International Journal of Economics and Financial Issues, 2016)
We introduce a set of time series analysis indicators under an event based framework of directional changes and overshoots. Our aim is to map continuous financial market price data into the so-called Directional-Change (DC) Framework- a state based discretization of basically dissected price time series. The DC framework analysis relied on understanding the price time series as an event-based process, as an alternative of focusing on their stochastic character. Defining a scheme for state reduction of DC Framework, we show that it has a dependable hierarchical structure that permits for analysis of financial data. We show empirical examples within the Saudi Stock Market. The new DC indicators represent the foundation of a completely new generation of financial tools for studying volatility, risk measurement, and building advanced forecasting and automated trading models. Keywords: directional changes, financial forecasting, automated trading, financial markets, Saudi Stock Market. JEL Classifications: G11, G14, G1